A Social Media-Based Mindfulness Psycho-Behavioral Intervention (MCARE) for Patients With Acute Coronary Syndrome: Randomized Controlled Trial - Huijing Zou; Sek Ying Chair; Bilong Feng; Qian Liu; Yu Jia Liu; Yu Xin Cheng; Dan Luo; Xiao Qin Wang; Wei Chen; Leiqing Huang; Yunyan Xianyu; Bing Xiang Yang (JMIR Publications, 2024)
BackgroundPsychological distress is common among patients with acute coronary syndrome (ACS) and has considerable adverse impacts on disease progression and health outcomes. Mindfulness-based intervention is a promising complementary approach to address patients' psychological needs and promote holistic well-being. ObjectiveThis study aims to examine the effects of a social media-based mindfulness psycho-behavioral intervention (MCARE) on psychological distress, psychological stress, health-related quality of life (HRQoL), and cardiovascular risk factors among patients with ACS. MethodsThis study was a 2-arm, parallel-group randomized controlled trial. We recruited 178 patients (mean age 58.7, SD 8.9 years; 122/178, 68.5% male) with ACS at 2 tertiary hospitals in Jinan, China. Participants were randomly assigned to the MCARE group (n=89) or control group (n=89). The 6-week intervention consisted of 1 face-to-face session (phase I) and 5 weekly WeChat (Tencent Holdings Ltd)-delivered sessions (phase II) on mindfulness training and health education and lifestyle modification. The primary outcomes were depression and anxiety. Secondary outcomes included psychological stress, HRQoL, and cardiovascular risk factors (ie, smoking status, physical activity, dietary behavior, BMI, blood pressure, blood lipids, and blood glucose). Outcomes were measured at baseline (T0), immediately after the intervention (T1), and 12 weeks after the commencement of the intervention (T2). ResultsThe MCARE group showed significantly greater reductions in depression (T1: β=-2.016, 95% CI -2.584 to -1.449, Cohen d=-1.28, P<.001; T2: β=-2.089, 95% CI -2.777 to -1.402, Cohen d=-1.12, P<.001) and anxiety (T1: β=-1.024, 95% CI -1.551 to -0.497, Cohen d=-0.83, P<.001; T2: β=-0.932, 95% CI -1.519 to -0.346, Cohen d=-0.70, P=.002). Significantly greater improvements were also observed in psychological stress (β=-1.186, 95% CI -1.678 to -0.694, Cohen d=-1.41, P<.001), physical HRQoL (β=0.088, 95% CI 0.008-0.167, Cohen d=0.72, P=.03), emotional HRQoL (β=0.294, 95% CI 0.169-0.419, Cohen d=0.81, P<.001), and general HRQoL (β=0.147, 95% CI 0.070-0.224, Cohen d=1.07) at T1, as well as dietary behavior (β=0.069, 95% CI 0.003-0.136, Cohen d=0.75, P=.04), physical activity level (β=177.542, 95% CI -39.073 to 316.011, Cohen d=0.51, P=.01), and systolic blood pressure (β=-3.326, 95% CI -5.928 to -0.725, Cohen d=-1.32, P=.01) at T2. The overall completion rate of the intervention (completing ≥5 sessions) was 76% (68/89). Positive responses to the questions of the acceptability questionnaire ranged from 93% (76/82) to 100% (82/82). ConclusionsThe MCARE program generated favorable effects on psychological distress, psychological stress, HRQoL, and several aspects of cardiovascular risk factors in patients with ACS. This study provides clues for guiding clinical practice in the recognition and management of psychological distress and integrating the intervention into routine rehabilitation practice. Trial RegistrationChinese Clinical Trial Registry ChiCTR2000033526; https://www.chictr.org.cn/showprojEN.html?proj=54693